Minecraft ebook - Monster, Sfé R. (Minecraft (2019), 2019)
The first Graphic Novel in the world of Gaming Phenomenon Minecraft! Tyler is your everyday kid whose life is changed when his family has to move from the town he's always known. Thankfully, Tyler has a strong group of friends forever linked in the world of Minecraft! Tyler, along with his friends Evan, Candace, Tobi, and Grace have been going on countless adventures together across the expanses of the Overworld and are in need of a new challenge. They decide to go on the Ultimate Quest—to travel to the End and face off against the ender dragon!